Brevi spunti introduttivi per una filosofia della democrazia nel terzo millennio (Società e diritti, 2024)
The author discusses the crisis of the democratic concept and structures in this contribution, highlighting the conflict between democracy as a method and as a value. Democratic practice is seen as a potential constraint, making the system more manageable but also vulnerable to manipulation. In the third millennium, democracy must be rethought from an anthropological dimension, focusing on individual and collective freedom, The role of education and the transmission of democratic values are emphasized as fundamental elements to preserve the concept of democracy. The author stresses the risk of reducing democracy to a mere procedure, at the expense of its essential value content, concluding that a philosophy of democracy must go beyond political practices and structures, focusing on an anthropological and value-oriented renewal, so that democracy can survive and thrive in the third millennium.